THE IMPACT OF INDOOR AIR QUALITY ON THE HEALTH OF CHILDREN IN SCHOOLS AND KINDERGARTENS (European Journal of Interdisciplinary Research and Development, 2025)
Indoor air quality is a critical environmental determinant of child health, particularly in schools and kindergartens where children spend a substantial portion of their daily time. Due to their developing respiratory and immune systems, children are especially vulnerable to indoor air pollutants, including particulate matter, carbon dioxide, volatile organic compounds, allergens, and microbial contaminants. Inadequate ventilation, overcrowding, and poor building maintenance may exacerbate indoor air pollution and increase health risks. This article aims to evaluate the impact of indoor air quality on the health of children in educational institutions, with a focus on schools and kindergartens. The review examines the relationship between indoor air pollutants and respiratory diseases, allergic conditions, impaired cognitive performance, and increased absenteeism among children. Particular attention is given to the role of ventilation systems, building characteristics, and environmental control measures in maintaining healthy indoor air conditions. Understanding the influence of indoor air quality on child health is essential for developing effective preventive strategies and improving the learning and well-being of children in educational settings.